Against continuity : Gilles Deleuze's speculative realism - Kleinherenbrink, Arjen (Speculative realism., 2019)
Repositions Deleuze as a forerunner to Speculative RealismAgainst Continuity is the first book to demonstrate that the beating heart of Gilles Deleuze's philosophy is a systematic ontology of irreducible, singular entities. This requires a radical break with decades of Deleuzian orthodoxy, according to which Deleuze's metaphysics revolves around the dissolution of discrete entities into a continuous world of flows and events.With reference to all of Deleuze's work, including published and untranslated seminars, as well as the recently published Lettres et autres textes, Arjen Kleinherenbrink critically compares Deleuze's ontology to seven related contemporary thinkers: Levi Bryant, Maurizio Ferraris, Markus Gabriel, Manuel DeLanda, Graham Harman, Tristan Garcia and Bruno Latour. These comparisons establish Deleuze as an important precursor to object-oriented speculative realism and open up exciting new avenues of thought for critics and supporters of Deleuze alike.Key FeaturesRadically repositions Deleuze as an early speculative realistExamines the similarities and differences between Deleuze and speculative realists including Levi Bryant, Manuel DeLanda, Graham Harman, Maurizio Ferraris, Tristan Garcia, Markus Gabriel and Bruno LatourConsiders all of Deleuze's published writings, including his seminars"